Euro area exports and imports: Do determinants of intra- and extra-EMU trade differ? - Heike Joebges; Evelyn Herrmann (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2008)
The attempt is to explain EMU exports and imports, treating the euro area as one single economy. EMU trade is analysed separately for intra- and extra-EMU trade. One result of this approach is that extra- and intra-EMU trade seem to follow a different pattern. Therefore, a separate estimation seems preferable. This is especially true for exports. For imports, the mistake made seems to be smaller. Interestingly, the aggregate of intra- and extra-EMU trade seems to be dominated by the pattern of extra-EMU trade, although both sub-aggregates are of a similar size: Estimation equations for aggregate EMU exports are quite similar to those for extra-EMU exports and the equations for aggregate EMU imports resemble those for extra-EMU imports.
urn:nbn:de:101:1-20080818188
Keywords: 330